2005
DOI: 10.1016/j.tsf.2005.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of RuO2/Ta2O5 thin film evolution by thermogravimetry combined with mass spectrometry

Abstract: The thermal evolution process of RuO 2 -Ta 2 O 5 /Ti coatings with varying noble metal content has been investigated under in situ conditions by thermogravimetry combined with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This suggests the formation of an amorphous phase. This result is expected based on thermogravimetric data showing that the tantalum oxide formation occurs at temperatures higher than 450°C [27] and complete Ta 2 O 5 crystallization occurs at temperatures around 700°C [3,27]. A similar result was observed for RuO 2 -Ta 2 O 5 films prepared by SD [4].…”
Section: Resultssupporting
confidence: 83%
“…This suggests the formation of an amorphous phase. This result is expected based on thermogravimetric data showing that the tantalum oxide formation occurs at temperatures higher than 450°C [27] and complete Ta 2 O 5 crystallization occurs at temperatures around 700°C [3,27]. A similar result was observed for RuO 2 -Ta 2 O 5 films prepared by SD [4].…”
Section: Resultssupporting
confidence: 83%
“…The evolution of twocomponent systems like RuO 2 -TiO 2 , RuO 2 -ZrO 2 and RuO 2 -Ta 2 O 5 film electrodes from isopropanolic solutions have been studied by thermoanalytical, mass spectrometric and infrared emission spectroscopic methods [14][15][16]. As to the formation of the tin oxide thin film and the IrO 2 -SnO 2 two-component system, thermogravimetric, mass spectrometric and infrared spectroscopic studies have been reported [17,18]. In almost all the previous works the precursors were dissolved in alcoholic solutions.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, the hydroxyl content of hydrous ruthenium oxide is critical to its pseudocapacitive behavior. We have determined the hydroxyl content of our materials using a combination of thermogravimetric analyses (TGA, see the Supporting Information) , infrared spectroscopy (IR), and solid-state proton ( 1 H) magic angle spinning (MAS) NMR spectroscopy. There have been a limited number of solid state NMR studies of hydrous RuO x .…”
Section: Resultsmentioning
confidence: 99%